Soft drink and fruit juice problems solved - Ashurst, P. R.; Hargitt, Robert; Palmer, Fiona (Woodhead Publishing in food science, technology, and nutrition., 2017)
Soft Drinks and Fruit Juice Problems Solved, Second Edition, follows the innovative question and answer format of the first edition, presenting a quick problem-solving reference. Questions like: Does the use of a preservative in a product mean that it does not need to be pasteurized? How much deviation from ingredient specification is needed to cause a noticeable alteration in product quality? What kinds of organisms will grow in bottled waters? When is it necessary to obtain expert assistance in the event of a contamination incident? are all answered in detail. The book's new introduction covers basic questions about soft drinks, their ingredients, and packaging. Additional new chapters expand on microbiological problems, shelf life and storage, and fruit juices and nectars, as well as product nutrition and health claims. Final chapters offer soft drink and fruit juice data sources. Written by authors with extensive industrial experience, the book is an essential reference and problem-solving manual for professionals and trainees in the beverage industry.